Draft genome sequences of Pseudomonas amygdali pv. loropetali pathotype strain DSM 105780 PT, isolated from Florida. Issue 9 (8th September 2022) - Parajuli, Apekshya; Harmon, Carrie L.; Minsavage, Gerald V.; Jones, Debra D.; Timilsina, Sujan; Paret, Mathews L.; Jones, Jeffrey B.
Abstract : The pathogen that causes stem gall in Loropetalum chinense was first identified in Florida and Alabama in 2018 and named Pseudomonas amygdali pv. loropetali . We report the genome sequence of the pathotype strain of this pathogen, Pseudomonas amygdali pv. loropetali DSM105780 PT .